PENINGKATAN KUALITAS DAN PRODUKTIVITAS MELALUI MSDM BERBASIS INOVASI PADA KALIBOTO GREEN INSTITUTE - Praptiestrini; Kim Budiwinarto; Yanti Sri Danarwati; Giarti Slamet; Sri Wahyu Ening Handayani; Siti Arifah (Surakarta Abdimas Journal, 2024)
This community service activity aims to improve quality and productivity at Kaliboto Green Institute, an institution that focuses on goat farming, fish farming, and fermented animal feed processing, through the implementation of innovation-based Human Resource Management (HRM). The program is designed to strengthen employee skills, improve operational efficiency, and encourage innovation in the production process. The activity implementation method consists of several stages, namely preparation, training, implementation, and monitoring and evaluation. The preparation stage includes coordination with stakeholders and development of training materials. In the training phase, employees are provided with knowledge and skills in applying innovative HRM techniques. Implementation involves the direct application of the management practices that have been taught. Monitoring is conducted periodically to evaluate the implementation and its impact. The results of these activities showed a significant improvement in employee skills, especially in terms of time management, resource management, and problem solving. Operational efficiency also improved, as evidenced by reduced production time and improved end-product quality. In addition, there was increased innovation in the livestock and farming processes, such as the adoption of new technologies and more efficient management methods. Evaluation of the activities revealed several challenges faced, including resistance to change from some employees and limited resources to support long-term implementation. Based on the results, it is recommended to conduct capacity building on an ongoing basis and increase support from management to ensure the sustainability of the program. The program has also had a positive impact on the welfare of the local community and can serve as a model for the development of other small and medium enterprises.